Pengaturan Mengenai Kedudukan Wakil Presiden Dalam Tugasnya Membantu Presiden - Pramiswari, Brigita Glori Putri; Ruslie, Ahmad Sholikhin (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The position of the Vice President in the Indonesian constitutional system is an important element in the presidential government. Although regulated in the 1945 Constitution, the role and function of the Vice President are often unclear, which can create ambiguity in the implementation of daily tasks. This study aims to analyze the functions and authorities of the Vice President, especially when the President is absent. As part of the executive, the Vice President is not only tasked with accompanying the President, but also has the responsibility in decision-making. However, although it has been regulated in the 1945 Constitution, the role and function of the Vice President are often unclear. So from this study there is one formulation of the problem, namely, what are the functions and authorities carried out by the vice president when the president is absent from carrying out his duties. This study uses a normative research method by seeking materials from various sources such as laws and regulations, books, and journals to examine the legal position of the Vice President and its implications in the implementation of the presidential system. So the results of this study indicate that the Vice President has a role in accompanying the President, coordinating policies between ministries, handling strategic issues, and representing the country in international forums.